2016
DOI: 10.1891/1052-3073.27.2.231
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitators to Saving Behavior in Low- to Moderate-Income Households

Abstract: The purpose of this study was to identify barriers and facilitators of saving behavior in low- to moderate-income households within a framework of predisposing, enabling, and reinforcing factors. Data used were from a U.S. Department of Agriculture/National Institute for Food and Agriculture–sponsored multistate project. With a sample of 757 low- to moderate-income households and hierarchical logistic regression, results indicated that enabling factors and reinforcing factors reduced the significance of predis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 40 publications
1
18
1
Order By: Relevance
“…Generally, as household income or lifetime earnings increases, the likelihood of saving increases (Avery & Kennickell, 1991;Chang, 1994;Henager & Mauldin, 2015;Rha et al, 2006;Yuh & Hanna, 2010). A similar relationship exists between household wealth and saving (Avery & Kennickell, 1991;Gutter et al, 2012;Mauldin et al, 2016;Yuh & Hanna, 2010). Homeowners were more likely to save than renters were (Fisher & Montalto, 2010;Rha et al, 2006;Yuh & Hanna, 2010).…”
Section: Other Factors Related To Saving Behaviormentioning
confidence: 96%
See 2 more Smart Citations
“…Generally, as household income or lifetime earnings increases, the likelihood of saving increases (Avery & Kennickell, 1991;Chang, 1994;Henager & Mauldin, 2015;Rha et al, 2006;Yuh & Hanna, 2010). A similar relationship exists between household wealth and saving (Avery & Kennickell, 1991;Gutter et al, 2012;Mauldin et al, 2016;Yuh & Hanna, 2010). Homeowners were more likely to save than renters were (Fisher & Montalto, 2010;Rha et al, 2006;Yuh & Hanna, 2010).…”
Section: Other Factors Related To Saving Behaviormentioning
confidence: 96%
“…On the other hand, some studies have found no relationship between financial knowledge and behavior or a limited effect of financial knowledge on saving behavior (Heckman & Hanna, 2015;Hilgert et al, 2003;Mandell & Klein, 2009;Mauldin et al, 2016). Heckman and Hanna (2015) studied factors related to low-income households' saving behavior and found that a higher level of financial literacy was not significantly associated with the likelihood of saving.…”
Section: Financial Knowledge and Saving Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have found savings to primarily be a function of income, wealth, and education (Turnham, 2010;Mauldin, Henager, Bowen, & Cheang, 2016). Latinos in this sample had lower levels of education and income, as well as a larger household size and number of children compared to white and black respondents.…”
Section: Discussionmentioning
confidence: 52%
“…Thus, policymakers must consider initiatives specifically targeting low‐income consumers, besides providing financial education. Studies conducted in the United States suggest that institutional factors, such as unemployment, lack of employer‐sponsored retirement plan, lack of comfort with financial institutions, lack of access to credit, and lack of motivation due to the present‐oriented time perspective are major factors that discourage the saving behavior of low‐income consumers, rather than a gap in financial knowledge (Heckman & Hanna, ; Mauldin, Henager, Bowen, & Cheang, ; Payne, ; Zimbardo & Boyd, ). To establish a new policy direction, future research comparing the impacts of financial literacy with institutional variables would be essential.…”
Section: Resultsmentioning
confidence: 99%